Nor Florist & Souvenir / Nur Zalikha Mohd Shahbuddin … [et al.] - Mohd Shahbuddin, Nur Zalikha; Roslan, Nur Natasya Syuhada; Zuber, Nur Nadiah; Abdul Shukor, Nurien Amyrah; Zakaria, Nur Afiqah (2022)
An executive summary offers an outline of the main points of a larger report. This report was completed to summarize the small company which is Nor Florist & Souvenir. Nor Florist & Souvenir is a floral shop that sells varieties of bouquets of fresh & artificial flowers. We chose Nor Florist & Souvenir as a focus subject for our case study. Case studies are important for evaluating company information, company analysis, major business problems, suggestions, and improvements. The methods that we utilized to study the analysis included conducting online interviews with the owner through WhatsApp to gain more information on what the business is all about and to understand the main fundamentals of the business operation. The elements will be represented using a strategic management tool namely the Business Model Canvas (BMC). The phase began by determining the basic idea and structure of the business process. The information gathered was classified into nine related dimensions and documented in accordance with the BMC. The generated BMC depicts the relationship of all the nine dimensions for the business run by Nor Florist & Souvenir. Based on the interviews, Nor Florist & Souvenir is a business owned by Puan Hazirah which has been in operation since 2012 and is located in Jalan Hang Tuah, Melaka. This business was started by her mother who really enjoys and loves to compose flowers. She may operate the same business and become successful because of her mother’s expertise. During the interviews, Puan Hazirah mentioned that her shop serves, sells, and delivers a variety of fresh flowers. They also provide other services such as fruit baskets, condolence wreaths, a new shop opening flower arrangements, newborn baby gifts, hand bouquets, gifts, congratulation gifts, Happy Birthday gifts, wedding decorations, and hampers. The business employs runners and part-time workers to provide the delivery services around Melaka. Nor Florist & Souvenir developed strengths, weaknesses, opportunities, and threats as the business was operated. Puan Hazira invests and takes risks upon any decision she makes and thus has complete control of her business. There were a few problems that occurred when she first started the business. Her business faced a lack of customer trust since it was still new and not well-known to others. Since the pandemic of Covid-19, there are a few advantages and disadvantages for them to continue operating their business. There are also a few suggestions for solving the challenges and barriers that are faced by Puan Hazirah’s business.